1999
DOI: 10.1021/ja9805829
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of Sc+(3D,1D) and V+(5D,3F):  Reaction of Sc+ and V+ with Water

Abstract: The study of the reaction of water with the early first-row transition metal ions has been completed in this work, in both high-and low-spin states. In agreement with experimental observations, the only exothermic products are the low-lying states MO + + H 2 ; formation of other endothermic products is also examine. An in-depth analysis of the reaction paths leading to each of the observed products is given, including various minima and several important transition states. All results have been compared with e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
86
2
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(100 citation statements)
references
References 37 publications
(39 reference statements)
11
86
2
1
Order By: Relevance
“…The potential-energy surface for the exothermic but spinforbidden dehydrogenation of D 2 O with ground-state V + ( 5 D) has been described previously by Armentrout et al 18 and Ugalde et al 26 The reaction path involves the initial formation of the ion dipole complex V + ‚OD 2 , which then isomerizes by insertion to form D-V + -OD, evolves through a four-centered transition state into VO + ‚D 2 , and then separates into the products VO + ( 3 Σ) + D 2 . The overall transformation involves a crossing to a low-spin triplet state located between the intermediate D-V +-OD and the V + ‚OD 2 complex and lies above the initial energy of the reactants.…”
Section: O-atom Transfer (Dehydrogenationmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential-energy surface for the exothermic but spinforbidden dehydrogenation of D 2 O with ground-state V + ( 5 D) has been described previously by Armentrout et al 18 and Ugalde et al 26 The reaction path involves the initial formation of the ion dipole complex V + ‚OD 2 , which then isomerizes by insertion to form D-V + -OD, evolves through a four-centered transition state into VO + ‚D 2 , and then separates into the products VO + ( 3 Σ) + D 2 . The overall transformation involves a crossing to a low-spin triplet state located between the intermediate D-V +-OD and the V + ‚OD 2 complex and lies above the initial energy of the reactants.…”
Section: O-atom Transfer (Dehydrogenationmentioning
confidence: 99%
“…21 Measurements of the energetics of hydration of alkali ions also were reported by Kebarle et al, who used high-pressure ion source (HPIS) mass spectrometry. [22][23][24] Systematic theoretical investigations using ab initio calculations designed to understand the reactivity of transition-metal cations with water have been reported by Ugalde et al 25 These authors have addressed quantum mechanical constraints introduced by spin-forbidden crossings of the potential energy surfaces that are involved in the formation of oxide cations in the reactions of water with Sc + and V + , 26 Cr + , 27 Mn + , 27 Fe + , 27,28 Co + , Ni + , and Cu + . 25 Similar surface crossings have been predicted very recently for the reaction of W + with water.…”
Section: Introductionmentioning
confidence: 99%
“…(6) have demonstrated that the experimentally observed reaction ef®ciency coincides with the probability of spin-inversion between the sextet and quartet surfaces [47a]. Occurrence of TSR has even been proposed in the reactions of early transition metals [38,54] for which spin-orbit coupling is lowest in the 3d series.…”
Section: General Considerations For Alkane Hydroxylationmentioning
confidence: 99%
“…Broad-band photolysis with a high-pressure mercury arc lamp yields the bare oxide VO [21]. The potential energy surfaces of water activation by first-row transition metal ions were calculated in a series of papers by Ugalde and coworkers [22][23][24][25][26], showing that the case of Fe + is a typical example of two-state-reactivity [27]. For V + , elimination of H 2 involves a curve crossing from the quintet to the triplet surface [24].…”
Section: Introductionmentioning
confidence: 99%
“…The potential energy surfaces of water activation by first-row transition metal ions were calculated in a series of papers by Ugalde and coworkers [22][23][24][25][26], showing that the case of Fe + is a typical example of two-state-reactivity [27]. For V + , elimination of H 2 involves a curve crossing from the quintet to the triplet surface [24]. According to the calculated energies, the adiabatic threshold for H 2 [28], and in all cases report that the structure of the studied species is a central metal ion with up to four solvating intact water molecules.…”
Section: Introductionmentioning
confidence: 99%